Building bridges through international mobility: a joint program between UiTM and Mulawarman University Indonesia - Wan Ibrahim, Wan Muhd Faez (UiTM Sarawak, 2024)
The Faculty of Business and Management of UiTM Sarawak hosted a one-day international mobility online program, bringing together undergraduate students from UiTM Sarawak and its MOU partner Mulawarman University Indonesia. The program featured lectures from academics from both universities on topics such as finance, economics, and marketing. This program offers invaluable opportunity for students from both universities to gain international exposure and understanding of their respective fields, while also providing a platform for cross-cultural collaboration and learning. Furthermore, it provides a platform for lecturers to exchange knowledge and experiences between the two universities, and hence helps to cultivate a collaborative and mutually beneficial relationship between the two institutions.